(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2023)
The nonlinear PI controller (NLPI) provides a better performance level compared to those of the most well-known algorithms for velocity and flux control. It is best suited to control the parameters of changing process characteristics. This article reports on developing an NLPI controller using the nonlinear function approach. Provide the theory, the algorithm used, the software aspects of the system implementation, and the results of simulation tests obtained on a process control system.